Minimal concentrations of aminoglycoside that can synergize with penicillin in enterococcal endocarditis. - Carrizosa, J (1981)
Minimal concentrations of aminoglycoside that could produce a synergistic effect with penicillin were investigated in broth cultures containing 10(8) enterococci per ml, in vitro in vegetations infected with ca. 10(8) enterococci per g, and in vivo in an experimental model of enterococcal endocarditis. Penicillin G plus gentamicin (1.5 or 0.75 microgram/ml) sterilized a broth culture of a streptomycin-resistant strain (E1) at 48 h. In contrast, penicillin G plus gentamicin (1.5 or 0.75 microgram/ml) sterilized only 2 of 15 in vitro vegetations at 5 days. Similarly, doses of gentamicin that resulted in peak serum levels of 1.5 microgram/ml failed after 10 days of therapy with penicillin G plus gentamicin to sterilize in vivo vegetations infected with E1, and doses of gentamicin that resulted in peak serum levels of about 8 micrograms/ml sterilized four of six vegetations. Similar results were obtained with a streptomycin-susceptible strain. These studies indicated that the rate of bactericidal activity in broth cultures is greater than the bacteriological response in infected vegetations and that aminoglycoside concentrations that appear efficacious on the basis of synergy studies in broth cultures may not be satisfactory clinically.